2005
DOI: 10.1080/08958370590885681
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Responses in Unrestrained WKY Rats to Inhaled Ultrafine Carbon Particles

Abstract: Based on epidemiologic observations, the issue of adverse health effects of inhaled ultrafine particles (UFP) is currently under intensive discussion. We therefore examined cardiovascular effects of UFP in a controlled animal exposure on young, healthy WKY rats. Short-term exposure (24 h) to carbon UFPs (38 nm, 180 microg m (-3)), generated by spark discharging, induced a mild but consistent increase in heart rate (18 bpm, 4.8%), which was associated with a significant decrease in heart-rate variability during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 48 publications
3
45
0
7
Order By: Relevance
“…This is 10-100-fold higher than ambient levels measured in polluted urban areas [8]. This mass concentration is in the range (170-1660 mg?m -3 ) applied in other toxicological studies identifying only mild inflammatory responses to UFP exposure [33,34]. The pro-inflammatory effects described in the current study could also be detected less pronounced at a lower particle burden of 180 mg?m -3 , e.g.…”
Section: Ultrafine Particle Inhalation Is Pro-inflammatory E André Ementioning
confidence: 51%
“…This is 10-100-fold higher than ambient levels measured in polluted urban areas [8]. This mass concentration is in the range (170-1660 mg?m -3 ) applied in other toxicological studies identifying only mild inflammatory responses to UFP exposure [33,34]. The pro-inflammatory effects described in the current study could also be detected less pronounced at a lower particle burden of 180 mg?m -3 , e.g.…”
Section: Ultrafine Particle Inhalation Is Pro-inflammatory E André Ementioning
confidence: 51%
“…Inhalation of ultrafine carbon particles (38 nm, 180 µg/m 3 for 24 hours) caused increased heart rate and decreased heart-rate variability in rats, but there was no inflammatory response and no change in the expression of genes having thrombogenic relevance (Harder et al, 2005). In spontaneously hypertensive rats exposed to similar ultrafine carbon particles (172 µg/m 3 for 24 hours), blood pressure and heart rate increased with a lag of 1-3 days.…”
Section: Toxicological Studiesmentioning
confidence: 95%
“…31 Ultrafine particles are associated with oxidative stress, 32 as well as with reduced HRV. 33 To better understand why exposure to ETS is associated with lower HRV, it is interesting to compare these effects with those of active smoking on HRV. In a recent publication, we showed that active smokers had lower overall and low to ULF HRV measures than never smokers, which reflect the dynamic features of sympathetic cardiovascular modulation, analogous to the results described in this work.…”
Section: Discussionmentioning
confidence: 99%